University Students’ Communication and Employability Skills: Mismatch Perspectives of Students, Lecturers, and Employers in Sarawak, Malaysia - Teresa Wai See Ong; Su-Hie Ting; Humaira Raslie; Ernisa Marzuki; Kee-Man Chuah; Collin Jerome (NOTION: Journal of Linguistics, Literature, and Culture, 2022)
In Malaysia, graduate unemployability is a problem that is often highlighted. Studies have shown that graduates lack soft skills, such as problem solving, English language proficiency, and communication skills, which contribute to the issue of unemployability. However, these studies have not investigated employability skills from all three perspectives of students, lecturers, and employers to understand whether students are developing the necessary skills to be more employable, and whether lecturers are getting it right when preparing their students for the job market. Therefore, this study fills in the gap by comparing university students’ communication and employability skills from the perspectives of students, lecturers, and employers. The study aimed to determine students’ ratings of communicative ability and employability skills, and how these ratings match those of the lecturers and employers, and to compare the ranking of the importance of these skills by lecturers and employers. The questionnaire data were collected from 123 students, 26 lectures, and 26 employers in Sarawak, Malaysia. The findings showed that the students rated themselves more highly on reading and writing, and employability skills than on listening and speaking skills. The lecturers and employers ranked employability skills as more important than communication skills. They were consistent in the ranking of interpersonal skills and presentation skills as the top communication skills. The top employability skills were time management skills, leadership qualities, managing personnel, managing resources, teamwork spirit, planning, organising, controlling and evaluation skills, and problem-solving aptitude. However, lecturers prioritised teamwork spirit while employers prioritised problem-solving aptitude. However, none of the reading and writing skills were among the top 10 skills expected of graduates entering the workplace. In concluding the study, the overall findings indicated that the students and lecturers overrated the students’ readiness for the workplace.